In vivo evaluation of titanium oxide and hydroxyapatite as an artificial cornea skirt - Tan, Xiao Wei; Beuerman, Roger W.; Shi, Zhi Long; Neoh, Koon Gee; Tan, Donald; Khor, Khiam Aik; Mehta, Jodhbir S. (Journal of materials science. Materials in medicine, 2012)
Keratoprosthetic devices are subject to chronic inflammatory, pathological processes and the external environment that affect their stability and biocompatibility with the ocular surface and adjacent ocular tissues. We compared the corrosion resistance property and tissue-implant reaction of titanium oxide (TiO 2 ) with hydroxyapatite (HA) in artificial tear fluid and a rabbit skin implantation model. The dissolution properties of the implant surfaces were evaluated with scanning electronic microscope (SEM) and atomic force microscope (AFM). Tissue inflammatory reactions were evaluated by Hematoxylin & Eosin staining, avidin biotin peroxidase complex (ABC) immunoassay and immunofluorescence. SEM and AFM images showed that there was less pitting corrosion on the surface of TiO 2 implants compared with HA. TiO 2 and HA exhibited a similar pattern of foreign body capsule formation and inflammatory cellular responses. The Collagen I/Collagen III ratio of the TiO 2 capsule was higher than that of the HA capsule. TiO 2 implants possess a high corrosion resistance property both in vitro and in vivo and the inflammatory cellular response to TiO 2 is similar to HA. With regards to corrosion resistance and inflammatory tissue responses, TiO 2 appears to be a promising material for keratoprosthetic skirt devices.